Approaches to the Real: The Didascalias in the Work of Beatriz Catani - Conde, Laura Gabriela (2025)
This paper presents a rhetorical-affective analysis of the stage directions in Beatriz Catani’s dramaturgy. From the perspective of Affect Theory, this involves considering to what extent the writing of this "unspoken" aspect of the dramatic text constitutes a figure that produces and records ways of experimenting with language, bodies, space, and time. In this sense, different rhetorical, syntactic, and semantic forms in the stage directions of some of her works—especially in Ojos de ciervo rumanos—are examined. It is argued that these forms allow an exploration of the aesthetic pursuits and procedures that express the sensibilities and transformations of her time: it expresses what the author herself recognizes as “approaches to the real” in response to the “crisis of theatrical representation”. Thus, this study proposes an analysis of stage directions as a sign “saturated with affect”, memory, images, and bodies.